Case Study: Language Politeness in Preschool Children at Ar-Rahman School - Yusrita Rahmi; Nurhikmah Adawiyah; Nusratova N. Dilaro (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: This research aims to investigate how preschool children use language politeness. The method used is a pragmatic approach with a qualitative approach. Language politeness is usually part of adult human abilities. Adults will be better able to judge whether an utterance is considered polite or not, depending on various factors such as social distance, culture, and power relations. Methodology: The data that has been copied and grouped is then analyzed using the politeness theory of language developed by Brown and Levinson. In qualitative research, data analysis begins with reducing data, categorizing data, presenting data, drawing conclusions from findings, and verifying. Main Findings: The research results show that language politeness can be divided into four main strategies. However, the results show that preschool children, especially those aged 3-5 years, do not fully understand the concept of politeness. The data obtained showed considerable variation in children's understanding of politeness strategies, without any clear consistency. Novelty/Originality of this study: The novelty of this research is the methodological approach that uses direct observation in various activity situations at school as well as in-depth interviews with teachers and parents, which provides a comprehensive picture of language politeness practices. This makes a significant contribution to academic literature and educational practitioners in understanding and developing language politeness from an early age.